A NEW SPECIES OF ISCHAEMUM FROM SULAWESI - Lasut, Marthen Theogives (Research Center for Biology, 2006)
LASUT, MARTHEN T. 2006. A new species of Ischaemum from Sulawesi. Reinwardtia 12(3): 257â259.ââA new species of Ischaemum veldkampii Lasut sp. nov. is described.